Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
[tex]f(x) = 4x^2-4x-3\\
f'(x)=\lim_{h\to0}\frac{f(x+h)-f(x)}{h}\\
f'(x)=\lim_{h\to0}\frac{4(x+h)^2-4(x+h)-3-(4x^2-4x-3)}{h}\\
f'(x)=\lim_{h\to0}\frac{4(x^2+2hx+h^2)-4x-4h-3-4x^2+4x+3}{h}\\
f'(x)=\lim_{h\to0}\frac{4x^2+8hx+4h^2-4h-4x^2}{h}\\
f'(x)=\lim_{h\to0}\frac{8hx+4h^2-4h}{h}\\
f'(x)=\lim_{h\to0}{8x+4h-4}\\
f'(x)=8x+4\cdot0-4\\
f'(x)=8x-4\\[/tex]
[tex]f'(x)= \lim_{h \to 0} \frac{f(x+h)-f(x)}{h} \\\\-----------------\\f(x)=4x^2-4x-3\\\\f'(x)= \lim_{h \to 0} \frac{4(x+h)^2-4(x+h)-3-(4x^2-4x-3)}{h}=\\\\=\lim_{h \to 0} \frac{4(x^2+2xh+h^2)-4x-4h-3-4x^2+4x+3}{h}=\\\\=\lim_{h \to 0} \frac{4x^2+8xh+4h^2-4x-4h-3-4x^2+4x+3}{h}=\\\\=\lim_{h \to 0} \frac{8xh+4h^2-4h}{h}=\lim_{h \to 0} (8x+4h- 4)=8x+4\cdot0-4=8x-4\\\\f'(x)=8x-4[/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.